PHILOSOPHY AND ROLE REFLECTION OF TEACHING PRACTICES IN THE COMMUNICATION SCIENCE EXTENDED DEGREE PROGRAMME. - Krige, D.; Bezuidenhout, J. (South African Journal of Higher Education, 2015)
Higher education teachers approach their teaching practices in accordance with how they conceptualise teaching and learning. Higher education teaching and learning literature contains numerous theoretical conceptions among others, Carnell's (2007) model of teaching and learning that identifies four approaches to teaching and learning: didactic, cooperative, empowering and community. In the Department of Communication Science at the University of the Free State (UFS), Bloemfontein, South Africa, students enrolled in the four-year extended degree programme (EDP) attend academic facilitation sessions (AFSs) to improve their academic competencies. Since these AFSs follow the teaching and learning philosophies of experiential learning, social constructivism and cooperative learning, the AFS activities were measured against Carnell's (2007) model to determine whether the teaching approaches used in the AFSs are in line with these underpinning philosophies as expressed in the model. Through critical self-reflection, the roles of the teacher and learners were identified and correlated to Carnell's model. The results of the analysis indicated that the current teaching approach is mostly empowering and cooperative and that teachers need to address the community approach in their teaching activities to build towards collective knowledge construction in the EDP.